Partai Kebangkitan Bangsa (PKB) dalam Menjawab Tantangan Multikultural di Indonesia : Studi Kasus Papua - Dewi, Nevy Rusmarina; Sholahuddin, Ahmad (State Islamic Institute of Kudus (IAIN Kudus), 2020)
Partai kebangkitan Bangsa (PKB) is one of the Islamic parties which has a fairly large mass in Indonesia. Its existence in Indonesia is very important to unite the multicultural nation of Indonesia. During Gus Dur's leadership, PKB opened many discourses on the issue of multiculturalism so that many people made PKB a role model in multicultural life. The method used in this study is a qualitative research method using literature study sources in the form of books, websites, articles and newspapers. One case that shows the attitude of PKB is multicultural is the Papua Conflict case. Recent cases have become very important issues for the sustainability of politics and governance in Indonesia. PKB gave a statement in overcoming this conflict, that the Indonesian government immediately resolve the issue. Multicultural open policy has become part of PKB in the political arena in Indonesia. In this article, we will discuss how PKB attitudes in political life in Indonesia, especially regarding attitudes in conflict in Papua.